The adoption of geographic information systems in the assessment and evaluation of geological and geomorphological sites, in the development horizon of tourism in the Great Atlas of the Middle: case of Valley of AitBougmez/ Morocco - Bouazza, Slack; Aref, Said; Khalaki, Yahya; Tawfiq, Ayat Omar (Journal of natural sciences, life and applied sciences, 2018)
This article deals with the use of geographic information systems in the field of tourism development, through the inventory of geological, geomorphological and geological sites, in Ait Bockmaz at the Great Atlas.The study was based on a quantitative scientific evaluation of the various sites, based on the method of the University Geological Institute of Lausanne, Switzerland 2007.The study builds on the assessment of scientific standards and the set of additional values ​​to monitor the importance of these sites in geo-political and geo-economic development,thus,The importance of this study is also reflected in the crystallization of a new thought which is the integration of land resources and the achievement of sustainable local development, also it is based on the technological information systems such as geology in defaming the mountain heritage in various components and introducing it locally, domestically and internationally, In the development horizon of tourism in general and geological tourism, geomorphic, and geological in particular.The study found nearly 14 inventory locations, additional scientific values and geo-touristic that vary from one location to another, the study was also keen to suggest some forms of the region's tourist valorization through a comprehensive tour round our dependence on GIS software.
Keywords: Middle High Atlas; Ait Boukamaz Depression; GIS; geological and geomorphological sites; method of the University Geographical Institute of Lausanne